Amides and neolignans from the aerial parts of Piper bonii. (September 2016) - Ding, Duo-Duo; Wang, Yue-Hu; Chen, Ya-Hui; Mei, Ren-Qiang; Yang, Jun; Luo, Ji-Feng; Li, Yan; Long, Chun-Lin; Kong, Yi
Abstract: Six amides, piperbonamides A–F, three neolignans piperbonins A–C, and 11 known compounds were isolated from the aerial parts of Piper bonii (Piperaceae). The structures of piperbonamides A–F and piperbonins A–C were elucidated based on the analysis of 1D and 2D NMR and MS data. Piperbonin A, (+)- trans -acuminatin, (+)- cis -acuminatin, (+)-kadsurenone, and pipernonaline showed weak activity against platelet aggregation with IC50 values of 118.2, 108.5, 90.02, 107.3, and 116.3 μM, respectively, as compared with the positive control, tirofiban, with an IC50 value of 5.24 μM. Piperbonamides A–F were inactive against five tumor cell lines at concentrations up to 40 μM. Graphical abstract: Six amides and three neolignans were isolated from Piper bonii . Several compounds showed weak activity against platelet aggregation induced by thrombin. Highlights: Six amides and three neolignans were isolated from Piper bonii . Several compounds showed weak activity against platelet aggregation induced by thrombin. The initial structure-activity relationships were discussed.